Nanomaterials from bacterial cellulose for antimicrobial wound dressing - Liyaskina, E; Revin, V; Paramonova, E; Nazarkina, M; Pestov, N; Revina, N; Kolesnikova, S (Journal of physics. Conference series, 2017)
Bacterial nanocellulose (BNC) is widely used in biomedical applications. BNC has attracted increasing attention as a novel wound dressing material, but it has no antimicrobial activity. To get over this problem in the present study the BNC was saturated with antibiotic fusidic acid (FA). The subject of the experiment was BNC, produced by bacteria Gluconacetobacter sucrofermentans B-11267. The resulting biocomposites have high antibiotic activity against Staphylococcus aureus and can be used in medicine as a wound dressing. The structure of BNC was analyzed by atomic force microscopy (AFM) and Fourier transform infrared spectroscopy (FTIR).